Аналіз перетворювача постійного струму, що працює на плазмову дугу - Верещаго, Євген Миколайович; Костюченко, Віталій Іванович; Новогрецький, Сергій Миколайович (Національний технічний університет "Харківський політехнічний інститут", 2023)
В роботі проведено аналіз стабілізованого перетворювача постійного струму, що працює на плазмову дугу. Обґрунтовано безперервну модель системи з урахуванням її особливостей. Визначені параметри незмінної частини під час аналізу схеми заміщення замкнутої структури системи електроживлення для дугового навантаження із від'ємним диференціальним опором. Проведені дослідження розімкнутої системи "джерело живлення - дуга". Встановлено, що розглянута схема з вихідними даними, прийнятими в даній статті, має частотний коефіцієнт передачі такого ж виду, що і немінімально-фазова ланка першого порядку. Отримано частотні характеристики вхідного та вихідного опорів перетворювача, навантаженого на дугу.

The article is devoted to the analysis of a stabilized direct current converter operating on a plasma arc. Electroplasma technologies of the new generation cause the need to design workable systems that provide control of technological processes and their dynamic optimization in real time. The improvement of any electroplasma technology begins with the improvement of the operating parameters of the main element of plasma installations – the power source. Goal is to build and study a continuous model of a pulsed source of secondary power supply, which works on an electric welding and plasma arc. Methodology. In the work, a mathematical description of the converter was performed. The continuous model of the system is substantiated, taking into account its features, namely, the load (gas-discharge gap) is a source of voltage and dynamic resistance. The parameters of the constant part during circuit synthesis are determined: the components of the gain of the constant part, the relative signal coefficient of the current sensor and the PWM gain. Studies of the open system «power source - arc» have been carried out. Results. MATLAB objects were created - continuous mathematical models of the object in the form of transfer functions. The obtained transient characteristics for different options: «arc current - control signal» and « inductor current - control signal» showed that open systems are unstable. It was found that in the case of instability, the filling frequency of self-oscillations occurring in the linear mode is close to the frequency of natural oscillations of the circuit. The dependence of the module and the argument of the input resistance of the power part of the pulsed power supply with parallel capacitance to the electric arc and without it, which have matching frequency characteristics, is established. The circuit considered with the initial data adopted in this article has a frequency transfer coefficient of the same type as the first-order non-minimum-phase (phase-shifting) link. Frequency response graphs for the output impedance of the power unit show that this power unit is a broadband frequency-selective system with a bandwidth of B0.707 = 100 kHz. Originality. Expressions for the frequency transfer function, input and output resistance of the pulse voltage converter operating on an arc load were obtained by the method of averaging and linearization. The frequency amplitude and phase characteristics for the pulse voltage converter with an LC filter and the output according to the arc current and the choke current were studied. The transfer functions of the continuous model in terms of arc current and choke current at the specified parameters are the same, which must be taken into account when designing regulators. Practical significance. The frequency characteristics of the input and output resistances and transfer functions can be used when forming a technical task for designing a power source to assess the stability of the «pulse converter - arc» system and rational calculation of input filters.
Analysis of a DC converter working on a plasma arc
Keywords: фільтр; імпеданс; система стабілізації; стійкість; filter; impedance; stabilization system; stability